2012
DOI: 10.1097/jcp.0b013e31823f8770
|View full text |Cite
|
Sign up to set email alerts
|

The Psychopharmacology of Aggressive Behavior

Abstract: Patients with mental disorders are at an elevated risk for developing aggressive behavior. In the last 19 years, the psychopharmacological treatment of aggression has changed dramatically because of the introduction of atypical antipsychotics into the market and the increased use of anticonvulsants and lithium in the treatment of aggressive patients.Using a translational medicine approach, this review (part 1 of 2) examines the neurobiology of aggression, discussing the major neurotransmitter systems implicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(57 citation statements)
references
References 144 publications
3
48
0
6
Order By: Relevance
“…These data are consistent with the preclinical literature in suggesting a facilitating role for glutamate in aggressive behavior (Comai et al, 2012). A synthesis of this work posits that glutamate can stimulate NMDA, AMPA, and metabotropic receptors in the amygdala, medial hypothalamus, and periaqueductal gray to enhance defensive-rage behavior.…”
Section: Discussionsupporting
confidence: 92%
“…These data are consistent with the preclinical literature in suggesting a facilitating role for glutamate in aggressive behavior (Comai et al, 2012). A synthesis of this work posits that glutamate can stimulate NMDA, AMPA, and metabotropic receptors in the amygdala, medial hypothalamus, and periaqueductal gray to enhance defensive-rage behavior.…”
Section: Discussionsupporting
confidence: 92%
“…To further understanding the mechanism of action of rapamycin, one possible approach would be to use either anti-epileptic or anti-psychiatric drugs as probes to selectively target each of them individually. However, there is an overt limitation in this method because many standard anti-epileptic drugs such as valproic acid and phenytoin not only suppress seizures, but also possess anti-psychiatric effect (Comai et al, 2012a, Comai et al, 2012b). Similarly, psychiatric drugs were also reported to have various effects on epilepsy (Ruffmann et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, studies in rodents have shown that the accumbal concentrations of this neurotransmitter are increased before, during and after an aggressive encounter (de Almeida et al, 2005). Clinical evidence has also shown the implication of hyperactive dopaminergic limbic transmission in reactive aggression (Comai et al, 2012). Furthermore, given the importance of accumbal dopamine signaling in habit formation, it is likely that this substrate may play a role in the formation of aggressive habits and the perpetuation of antisocial behaviors.…”
Section: Neurochemical Bases Of the Link Between Maoa And Aggressionmentioning
confidence: 99%